Fenomena Pengangguran Terbuka di Kabupaten Aceh Barat - Sartika, Dina; Ansari, Leli Putri (Regress: Journal of Economics & Management, 2022)
This article aims to discuss the phenomenon of open unemployment in West Aceh District seen from the variable factors of the minimum wage and the human development index (IPM). The problem with the phenomenon of open unemployment that occurs is the large number of open unemployed graduates caused by minimum wage factors and the human development index (IPM). The research method used is a secondary time series data type in the period 2012-2020. This research is a quantitative study using a multiple linear regression analysis model. The results of the study show that the minimum wage in West Acah Regency has a significant negative effect on open unemployment and for the Human Development Index (IPM) it has a significant negative effect on open unemployment.